2001
DOI: 10.1557/jmr.2001.0224
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies in combustion synthesis of NiAl–TiB2 composites: Effects of gravity

Abstract: Combustion synthesis (CS) of NiAl-based materials reinforced by TiB 2 particles was investigated under both terrestrial and microgravity conditions. The synthesized metal matrix composites (MMC) are characterized by very fine (<1 m) reinforced particulates, which have strong bonding along their entire surface with matrix (NiAl) and are distributed uniformly in it. It was found that microgravity leads to a decrease in the average TiB 2 particle size, while higher volume fraction of NiAl component in the materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…It has been shown that products with finer and more uniform microstructure are typically obtained under low-gravity conditions with respect to terrestrial ones. 10,11,21,24 The main experimental results related to the synthesis of the composites TiB 2 -xTiAl and TiB 2 -xTiAl 3 , under both terrestrial and low-gravity (10 Ϫ2 g where g is the terrestrial gravity acceleration) conditions are first reported in this work. Experiments under low-gravity conditions have been performed during the 32 nd ESA Parabolic Flights Campaign (Bordeaux, March 2002).…”
Section: The Results Obtained During a Parabolic Flight Campaign Sponmentioning
confidence: 84%
See 3 more Smart Citations
“…It has been shown that products with finer and more uniform microstructure are typically obtained under low-gravity conditions with respect to terrestrial ones. 10,11,21,24 The main experimental results related to the synthesis of the composites TiB 2 -xTiAl and TiB 2 -xTiAl 3 , under both terrestrial and low-gravity (10 Ϫ2 g where g is the terrestrial gravity acceleration) conditions are first reported in this work. Experiments under low-gravity conditions have been performed during the 32 nd ESA Parabolic Flights Campaign (Bordeaux, March 2002).…”
Section: The Results Obtained During a Parabolic Flight Campaign Sponmentioning
confidence: 84%
“…Specifically, as compared to the corresponding behavior on the ground, combustion wave typically travels slower under reduced gravity. 8,10,11,13,14,21,24 Moreover, under terrestrial conditions, bottom ignition of the sample results in a highercombustion velocity with respect to top ignition, 8,10,14,24 so that the following inequality holds:…”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…His initial research interest was focused on mathematical modeling of combustion fronts. However, very quickly his research evolved toward experimental investigation of reaction kinetics of heterogeneous reactions as well as understanding of system heterogeneity and melting effects on propagation of combustion fronts in the condensed phase [163][164][165][166][167][168][169][170][171][172][173][174][175][176][177]. Professor Varma invited a few Russian scientists, including Drs.…”
Section: Combustion Synthesis Research In Usa After 1980mentioning
confidence: 99%